2023
DOI: 10.29333/ejmste/13304
|View full text |Cite
|
Sign up to set email alerts
|

Learning styles in science education at university level: A systematic review

Albina R. Shaidullina,
Natalia A. Orekhovskaya,
Evgeny G. Panov
et al.

Abstract: In this systematic review study, it is aimed to summarize the findings and reach a conclusion about the role and importance of learning styles in science education at university level from 2007 to 2023. This paper analyzed the studies related to the learning styles in science education at university level. The original studies were extracted from Scopus database, and the review of the 21 selected journal articles revealed that the common feature of the studies in both groups was that learning styles in science… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Efforts have also been made to identify, analyze, and facilitate the alignment of these styles to improve the quality of postgraduate education [8]. Through a bibliometric study of systematic review, which summarizes findings on the role and importance of learning styles in scientific education at the university level from 2007 to 2023, it is confirmed that learning styles have a positive effect on both cognitive and affective factors [9].…”
Section: Introductionmentioning
confidence: 98%
“…Efforts have also been made to identify, analyze, and facilitate the alignment of these styles to improve the quality of postgraduate education [8]. Through a bibliometric study of systematic review, which summarizes findings on the role and importance of learning styles in scientific education at the university level from 2007 to 2023, it is confirmed that learning styles have a positive effect on both cognitive and affective factors [9].…”
Section: Introductionmentioning
confidence: 98%
“…In medical education, understanding learning styles is crucial for optimizing the learning process and ensuring that students effectively acquire the necessary knowledge and skills [9]. Previous studies have investigated the relationship between learning styles and academic performance in medical school, aiming to identify if certain learning styles are more favorable to succeed [10][11][12]. A systematic review found that medical students with con-verging and assimilating learning styles performed better in problem-based learning sessions compared to those with diverging and accommodating styles [10].…”
Section: Introductionmentioning
confidence: 99%